Regulatory Effect of Lactiplantibacillus plantarum 2-33 on Intestinal Microbiota of Mice With Antibiotic-Associated Diarrhea - Bao, Wuyundalai; He, Yuxing; Yu, Jinghe; Liu, Mingchao; Yang, Xiaofeng; Ta, Na; Zhang, Enxin; Liang, Chengyuan (Frontiers in Nutrition, 2022)
Diarrhea is one of the common adverse reactions in antibiotic treatment, which is usually caused by the imbalance of intestinal flora, and probiotics play an important role in the structure of intestinal flora. Therefore, this experiment studied the regulatory effect of Lactiplantibacillus plantarum 2-33 on antibiotic-associated diarrhea (AAD) mice. Firstly, the AAD mice model was established by the mixed antibiotic solution of gentamicin sulfate and cefradine. Then, the physiological indexes and diarrhea of mice were observed and recorded by gastric perfusion of low dose (1.0×107 CFU/mL), medium dose (1.0×108 CFU/mL) and high dose (1.0×109 CFU/mL) strain 2-33. 16S rRNA genes V3-V4 regions were sequenced in colon contents of mice in control group, model group, self-healing group and experimental group, respectively, and the diversity of intestinal flora and genes function prediction were analyzed. The results showed that the intestinal flora of AAD mice was not significantly regulated by gastric perfusion of strain 2-33 to 7 days, but the relative abundance and diversity of intestinal flora of AAD mice were significantly improved by gastric perfusion to 14 days (p<0.05). In addition, at the genus level, the relative abundance of Lactobacillus increased significantly, and the relative abundance of Enterococcus and Bacillus decreased significantly (p<0.05). In addition, the regulation of strain 2-33 on intestinal flora of AAD mice was time and dose dependent, short-term gastric perfusion and low dose had no significant effect (p>0.05). Strain 2-33 can significantly increase the levels of anti-inflammatory cytokines IL-4 and IL-10, significantly decrease the levels of pro-inflammatory cytokines TNF-α and IFN-γ (p<0.05), and can also adjust carbohydrate metabolism, amino acid metabolism and energy metabolism to normal levels, thus accelerating the recovery of intestinal flora structure of AAD mice. In summary, strain 2-33 can improve the structure and diversity of intestinal flora of AAD mice, balance the level of substance and energy metabolism, and play a positive role in relieve diarrhea, maintaining and improving the intestinal microecological balance.